Eukaryotic translation initiation factor 3 subunit D overexpression is associated with the occurrence and development of ovarian cancer. Issue 12 (31st October 2016) - Lin, Yaying; Zhang, Rongrong; Zhang, Ping
Abstract : Ovarian cancer is the most common cause of gynaecological cancer‐associated death; thus, promising biomarkers and new therapeutic targets for ovarian cancer must be explored. Here, we report that eukaryotic translation initiation factor 3 subunit D (EIF3D), a member of the EIF3 family, was overexpressed in ovarian cancer clinical tissues. Furthermore, the expression of EIF3D was correlated with the International Federation of Gynecology and Obstetrics stage and pathological differentiation stage. 3‐(4, 5‐dimethylthylthiazol‐2‐yl)‐2 (MTT) and colony formation assays revealed that the lentivirus‐mediated knockdown of EIF3D suppresses cell proliferation in the ovarian tumour cell lines CAOV‐3 and SKOV‐3. Flow cytometry revealed that cells were arrested at the G2/M phase of the cell cycle and that cyclin‐dependent kinase 1 was also altered after EIF3D silencing. The results presented here demonstrate that EIF3D may play an important role in the occurrence and development of ovarian cancer. Abstract : This study revealed that eukaryotic translation initiation factor 3 subunit D (EIF3D) was overexpressed in ovarian cancer tissues correlated with the International Federation of Gynecology and Obstetrics stage and pathological differentiation stage, and lentivirus‐mediated knockdown of EIF3D suppresses cell proliferation in the ovarian tumour cell lines by arresting the cell cycle at the G2/M phase. This demonstrates that EIF3D may play an important role in the occurrence and development of ovarian cancer.